Virilio’s Parting Song: The Administration of Fear and the Privatisation of Communism through the Communism of Affect - Athina Karatzogianni; Andrew Robinson (Media Theory, 2019)
In The Administration of Fear (2012), Virilio returns to his old 1977 theme of speed as the driving force in politics. For Virilio, modern power involves ever-accelerating speed, but in this work he takes it further by arguing there is a ‘cult of speed’, which is not progress but its ideology, whereby fear is hidden by the ideology of progress. Speed’s impact is mediated by affect, which produces social effects, such as loss of continuous action, ecological destruction, devitalisation, placelessness, fractal fragmentation, and group nationalisms or communalisms. This situation becomes particularly dangerous when the affective structures, which become viral are those – so common in turbo-capitalism – of fear, panic and hatred. As a result of telepresence, there is a ‘synchronisation of emotion’ which goes beyond the earlier standardisation of opinion. Virilio christens this regime the ‘communism of affect’ leading to new forms of politics: transition from a democracy of opinion to a democracy of emotion. In this article, we elaborate on this line of argumentation, and then discuss how Virilio may resonate and inspire analysis of contemporary political phenomena, such as affective polarisation in anti-immigrant fears driving the far right in Anglo-Saxon politics, securitisation in France, developmentalist acceleration and telepresence in India, and the dystopian extremes of the Chinese model.